Environmental factors in the summer Olympics in historical perspective - Peiser, B.; Reilly, T. (Journal of Sports Sciences, 2004)
A descriptive approach is adopted in reviewing the probable impact of environmental factors during the summer Olympic Games since their inception in 1896. A historical analytical perspective is impractical due to the lack of reliable climatic data for the earlier Games and the evolution of a myriad of factors that impinge on competitive performance at elite level. Nevertheless, the endurance running events, particularly the marathon, are considered in detail with respect to exposure to environmental forces. Heat, humidity, air pollution, altitude and the geographical features of the race course are considered selectively and dealt with in order of chronology and global climatic zones. We focus on diverse climate zones and particular environmental conditions in order to scrutinize their likely influences on competitive performance, especially in the Olympic marathon races. Notwithstanding the limitations of a narrative approach, performances are related to particular weather data and mitigating influences. Travel difficulties are addressed where these affected a majority of competitors. Environmental stress was associated with the ill-timing and poor organization of the earlier Games. While many of these detrimental and injurious features have been alleviated since then, other environmental stress factors are less prone to mitigation and thus remain a sometimes severe challenge to endurance races. The unique environment conditions for outdoor endurance races in temperate climate zones tend to be highly variable and therefore difficult to predict.